A Toolbox for Archaeological Heritage Management. Maps, Methods and More for Effective and Efficient Selection of Valuable Archaeology - R.C.G.M. Lauwerier; M.C. Eerden; B.J. Groenewoudt; M.A. Lascaris; E. Rensink; B.I. Smit; B.P. Speleers; J. Van Doesburg (Internet Archaeology, 2018)
With the aim of providing knowledge for informed choices, a series of tools have been developed for archaeological heritage management in the Netherlands. They include maps, datasets, methods, guidelines, best practice and web-based applications to facilitate the effective and efficient selection of valuable archaeological remains. The products relate to archaeological predictive modelling, disturbances by agriculture and other activities, archaeological heritage maps, prospection methods, research questions and scientific syntheses to close the archaeological heritage management cycle.